2021
DOI: 10.1371/journal.pone.0260950
|View full text |Cite
|
Sign up to set email alerts
|

Which representations of their gender group affect men’s orientation towards care? the case of parental leave-taking intentions

Abstract: Men are currently underrepresented in traditionally female care-oriented (communal) engagement such as taking parental leave, whereas they are overrepresented in traditionally male (agentic) engagement such as breadwinning or leadership. We examined to what extent different prototypical representations of men affect men’s self-reported parental leave-taking intentions and more generally the future they can imagine for themselves with regard to work and care roles (i.e., their possible selves). We expected prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 118 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…Most importantly, we report on cross-sectional correlational data and are therefore not able to draw causal conclusions about precursors of men’s intended leave-taking. Although experimental designs allow for such conclusions, they can be ethically questionable and difficult to implement for life decisions such as parenthood and parental leave-taking (for experimental evidence for hypothetical leave-taking, see Rudman and Mescher, 2013 ; Scheifele et al, 2021 ). The current study adds to existing research by examining intentions of men who are actually becoming parents and are facing parental leave-taking decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, we report on cross-sectional correlational data and are therefore not able to draw causal conclusions about precursors of men’s intended leave-taking. Although experimental designs allow for such conclusions, they can be ethically questionable and difficult to implement for life decisions such as parenthood and parental leave-taking (for experimental evidence for hypothetical leave-taking, see Rudman and Mescher, 2013 ; Scheifele et al, 2021 ). The current study adds to existing research by examining intentions of men who are actually becoming parents and are facing parental leave-taking decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on theories on the formation and change of social norms and SRT, it can be argued that a shift in the observed behavior of people around us can change social norms (Cialdini & Trost, 1998;Diekman & Eagly, 2000). In the context of gender, it has repeatedly been shown that beliefs about norms are dynamic and open to development (Koch et al, 2005;Scheifele et al, 2021;Sczesny et al, 2007;Twenge, 2001). For instance, threatening environmental factors and major social change can influence gender norms (Zafra & Garcia-Retamero, 2011).…”
Section: Changes In Norms About Gender Due To the Pandemicmentioning
confidence: 99%
“…One factor regards norms about gender roles regarding care responsibilities (Javornik and Kurowska, 2017; Tavits et al, 2023). Although there are new norms about active fatherhood, and shared care responsibilities between parents, these ‘new ideals for manhood and fatherhood have not fully replaced traditional norms and stereotypes’ (Scheifele et al, 2021: 2). In a recent study, Valarino and Gauthier (2016) examined the influence of compensated paid leave for fathers in Switzerland.…”
Section: Literature Review and Theorization Of ‘Instrumental Resource...mentioning
confidence: 99%